THE OPPORTUNITIES OF ARTIFICIAL INTELLIGENCE TECHNOLOGIES AND THEIR INFLUENCE ON YOUTH SPIRITUAL DEVELOPMENT - Oripov Khasan; Nosirova Gulbeka (Sciental Journals Publishing, 2026)
The development of modern society is closely linked to the rapid advancement of artificial intelligence technologies. Today, artificial intelligence is deeply integrated into the systems of education, economy, healthcare, culture, and social relations. In particular, young people, as the most active users of these technologies, are increasingly exposed to both the opportunities and risks associated with artificial intelligence. This article provides a comprehensive scientific analysis of the key capabilities of artificial intelligence technologies, their role in the lives of young people, as well as their positive and negative impacts on the moral and ethical development of youth.
Keywords: Artificial intelligence, digital technologies, youth, spirituality, ethics, education, social networks.